Anatomical Points of Cupping Therapy for Musculoskeletal Pain: A Systematic Review - Aris Setyawan; Isma Nur Hikmah; Eka Oktavianto; I Made Moh. Yanuar Saifudin (Nurse Media: Journal of Nursing, 2022)
Background: The prevalence of musculoskeletal pain is rising and plays a substantial role in disease and disability worldwide. There have been several previous studies on cupping therapy’s effectiveness in reducing musculoskeletal pain. However, studies that specifically review the literature on cupping points to reduce musculoskeletal pain are lacking.